Anamneza in preiskave v proktologiji - Mlakar, Boštjan (Medicinski razgledi, 2008)
The pathology of the anorectum is rich. Evaluation of some symptoms frequentlyassociated with diseases of the anus and rectum is presented. The general principles of history taking and digitorectal examination are discussed.
Keywords: Anus Diseases; Anus, bolezni; Diagnosis; Anamneza; Rectal Diseases; Rektalne bolezni; Fizikalna preiskava; Medical History Taking; Physical Examination; anus; diagnostika